Learning Strategies Through Babbling Techniques to Improve Language Comprehension Ability in Deaf Children at YPLAB SLB Lembang West Java - Ridwan, Prinanda Gustarina; Novianti, Ranti; Koestieni, Eny (Department of Special Education, 2023)
Language is a symbol of the referee sound used by members of social groups to work together, communicate, and identify themselves. The main function of language is as a means of communication between humans. With language will facilitate communication between individuals. This is not owned by deaf children. They have difficulty in language skills, especially in abstract understanding. So that deaf children must be given optimal educational services. Based on the language development of deaf children it stops in the groping or babbling phase so that their language experience is very limited. As a result, they have difficulty understanding language and communicating less than optimally. The language in question is the ability of deaf children to understand receptive and expressive language. For this reason, learning strategies are needed to improve language comprehension skills with palpation techniques. The babbling technique is an alternative in this learning because the syllable repetition technique makes deaf children able to think, combine letters into word structures. So that children can understand the word well. This research is based on the barriers of deaf children in understanding language, so a learning strategy is made with the results of field needs analysis. The method used uses research and development (R&D). The results of the field data show that learning strategies using babbling techniques can improve the ability of deaf children to understand language. This can be seen from the increase in the ability of deaf children to recognize syllables, words and being able to understand stories before and after being given learning through the babbling technique. Therefore, through appropriate learning strategies, they can develop their potential comprehensively.